From rhetoric to action : implementing the UN Convention on the Rights of Persons with Disabilities / Eilionóir Flynn. - Flynn, Eilionóir, 1986- (Cambridge disability law and policy series., 2011)
This book contains a global comparative study of implementation and monitoring mechanisms for national disability strategies. It comprises a comparative study that was conducted at international, regional and comparative country levels and that highlights critical success factors in implementing disability strategies or action plans worldwide. It explores emerging synergies between what is required to implement principles of international law contained in the Convention on the Rights of Persons with Disabilities and what it is possible to achieve through national policy and systems development. A number of critical success factors for implementing and monitoring strategies are identified, including leadership from government and civil society, participation of disabled people in implementation and monitoring, transparency and accountability in reporting on progress, independent monitoring and external review, and the ability to measure progress with indicators of disability equality.